Efficient removal and separation of cationic dyes by microbubbles for electroflotation coupling membrane electrosorption - Xue, Yuzhou; Feng, Mengru; Ding, ZiMo; Wang, Xuanxuan; Liu, Qing; Zuo, Yiling; Liu, Na; Qi, Yujie; Tang, Shurong (Separation and purification technology, 2025)
[Display omitted] •Electroflotation and electrosorption processes were highly effective in the removal of cationic dyes.•This removal process constituted a physical separation technique.•The zeta potential properties of microbubbles and the influence of the electric field were crucial.•The smart and straightforward method was provided to visually capture microbubbles for the first time. In order to enhance the treatment efficiency of cationic dyes wastewater, a dual chamber reactor was ingeniously designed to combine electroflotation and electrosorption technologies. The electrochemical system effectively removed representative single and mixed cationic dyes within 64 min at 150 mA. The observable reaction process phenomena, microbubble photos, clear Tyndall effect phenomena, and electrochemical experimental results all indicated the crucial role of electroflotation in removing cations dyes. Furthermore, changes in surface color, morphology, and functional groups of the anion exchange membrane before and after electrolysis suggested that the electrosorption process also contributed significantly to the removal process. Analysis using UV–vis absorption spectrum and high-resolution mass spectroscopy indicated that no significant chemical reaction occurred with the cationic dye during this process; thus, confirming that the separation of the cationic dye was a physical removal process. This study provides valuable theoretical guidance for efficient removal and separation of cationic dyes in wastewaters.